Transformation of Traditional Food and Beverage Industry with Industry 4.0 Approach: Case Study on Culinary Business in Bandung Area - Effendi, Marwan; Jasman, Jasman; Utami, Eva Yuniarti; Judijanto, Loso (West Science Journal Economic and Entrepreneurship, 2023)
The advent of Industry 4.0 has precipitated transformative changes in traditional industries globally. This research investigates the impact of Industry 4.0 on the traditional food and beverage sector in Bandung, Indonesia, with a focus on technological adoption, operational efficiency, customer engagement, and business performance. Through a quantitative approach involving 121 culinary establishments, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the complex interplay of these factors. The results indicate a positive and significant relationship between technological adoption and operational efficiency. Operational efficiency, in turn, correlates positively with customer engagement, leading to improved business performance. The study provides nuanced insights into the varied dynamics across different culinary segments and emphasizes the pivotal role of Industry 4.0 in shaping the competitive landscape of Bandung's culinary businesses.